Cancer‐associated fibroblasts show heterogeneous gene expression and induce vascular endothelial growth factor A (VEGFA) in response to environmental stimuli. Issue 4 (9th April 2019) - Inoue, Ken‐ichi; Kishimoto, Satoko; Akimoto, Kazumi; Sakuma, Masashi; Toyoda, Shigeru; Inoue, Teruo; Yoshida, Ken‐ichiro; Shimoda, Mitsugi; Suzuki, Shuji
Abstract: Aim: Cancer‐associated fibroblasts (CAF) play a crucial role in angiogenesis in the complex tumor microenvironment. However, fibroblasts show extensive heterogeneity and their dynamic functions against stressors remain largely unknown. Methods: We collected patient‐derived CAF and carried out perturbation‐based monitoring of the dynamic functions. Clinically relevant experimental stimuli were defined as follows: hypoxia, cisplatin, fluorouracil, coculture with cancer spheroids (interaction through paracrine signals). We selected 18 marker genes that encode components for fibroblast activation, intracellular communication, and extracellular matrix remodeling. Quantitative reverse transcription polymerase chain reaction was carried out for data collection and statistical analyses were carried out using SPSS software. Results: Kruskal‐Wallis multivariate analysis of variance showed that variations in expression of 11 marker genes were explained, in part, by a difference in tissue of origin. Friedman and two‐sided Wilcoxon signed rank tests detected significant perturbations in expression of marker genes. Paracrine signal from cancer spheroids induced vascular endothelial growth factor A ( VEGFA ) in CAF but not in fetal lung fibroblasts. Conclusion: We have established perturbation‐based monitoring of patients' CAF. Further data collection and individual patient follow up is ongoing to identify critical determinants of disease outcome. Abstract : VEGFA, a gene for angiogenesis was induced by experimental stimulus in cancer‐associated fibroblasts. Paracrine signal from cancer tissue‐originated spheroids was not sufficient for the induction in human fetal lung fibroblasts.